SP3.1.9 Implementation of colon capsule endoscopy (CCE) into the clinical setting – an early analysis. (9th August 2022) - Pollock, Alasdair; Pollock, William; Moug, Susan; Winter, Jack; Boulton-Jones, Rob; Witherspoon, Paul
Abstract: Aim: Analysis of the collaborative implementation of colon capsule endoscopy (CCE) within NHS Greater Glasgow and Clyde Methods: Database collected prospectively from first 175 patients referred. Demographic data collected for those undergoing CCE. Primary outcomes: negative, positive and incomplete/complications. Secondary outcomes: those requiring further investigation and outcomes (normal, abnormal and not performed). Abnormal findings: benign disease, dysplastic changes, malignancy and unresulted. Results: Of the first 175 patients put forward for CCE, 128 (73%) underwent CCE: n=47 deemed unsuitable due to patient preference (n=21) and consultant decision (n=15). Mean age 57.8 (+/-13.9 SD), 56% female, 32% had ≥2 co-morbidities, and 6% having colorectal cancer family history. CCE findings: negative 16% (n= 21), positive 71% (n=91), incomplete/complications 12.5% (n= 16). Time from referral to CCE (Mean 130 days, Median 86 days). Time from CCE to reporting (Mean 9.4 day, Median 8 days). Time from referral (CCE report) to colonoscopy (Mean 127 days, Median 106 days). Colonoscopies still awaited (Mean 271 days, Median 269 days). 80% required further tests: 77% (n=98) colonoscopy or sigmoidoscopy and 4% (n=5) imaging. Results: 20% normal, 48% abnormal, 30% not yet performed and 2% inadequate/no longer required. Pathology: benign disease 38%, dysplastic changes 45%, invasive malignancy 9%, 9% unreported. Conclusions: CCE has received significant investment to attempt to reduce the workload of endoscopy departments. However, 77% of the patients who underwent CCE require further investigation by scope. With an excellent safety profile, defining patient selection is key to optimising the clinical applicability of this evolving technology.